(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
When dealing with education and teaching in The technology of teaching (1968), Skinner considers the ideas of several authors, among which Rousseau, whom he mentions in more than half the chapters of the book. In this article, we analyse the context in which Skinner cites Rousseau, which themes is he dealing with when he does so, what is the role of the citations within the text, and what is Skinner’s position about what he cites of Rousseau. The reading of the complete original edition of the book allowed the identification of Skinner’s citations of Rousseau, which were, then, analysed. It was possible to verify that Skinner’s position on what he cites of Rousseau is negative in about half of the cases, and positive in the other half. The occurrences in which his position is negative refer, with only one exception, to the use of contrived versus natural contingencies of reinforcement. The occurrences in which his position is positive refer to a wider variety of themes.